Sekolah Islam Terpadu; Filsafat, Ideologi, dan Tren Baru Pendidikan Islam di Indonesia - Suyatno (Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2013)
Toward the 21st century, there is an interesting change in the trend of education (read Islamic education) in Indonesia. The dominance of educational institutions that consists of “Pesantren”, “Madrasah”, and Schools become different. It is based on the phenomenon that there are Integrated Islamic Schools in this country. The educational institutions, which have been spread to all parts of Indonesia, were established by some mosque activists at the ITB and UI campuses. The very rapid development of this school indicates that the Integrated Islamic School becomes the new trend of Islamic education in Indonesia. In this school, it is emphasized on the education of religious moral values and the excellent modern education nowadays. This kind of Integrated Islamic School has also proved a new style of the middle Islamization class of Indonesian Muslims.